An Assistance in Making Educational Game Tools for Teacher Raudlatul Athfal in Developing Children's Scientific Literacy in Metro Lampung City - Yuning Eka Rahma Wati; Suhono, Suhono; Najah Baroud; Yeasy Agustina Sari (International Journal of Community Engagement Payungi, 2025)
The lack of skills in utilizing environmentally friendly waste materials effectively and efficiently remains a challenge among early childhood educators. Many teachers in Raudlatul Athfal (RA) and Kindergarten have not yet received consistent and in-depth training on the optimization of interactive learning media. This study aims to identify concrete steps in the development of educational game tools (Alat Permainan Edukatif/APE) and to evaluate the impact of mentoring programs on the creation and implementation of APE in enhancing scientific literacy among early childhood learners in Metro, Lampung City. The mentoring program adopts the Asset-Based Community Development (ABCD) approach, which focuses on leveraging available assets—individual skills, natural resources, and existing infrastructure—to empower the community. The results show that the creation and use of APE by RA teachers play a strategic role in fostering children’s scientific literacy. These tools allow children to explore scientific concepts in an engaging, hands-on, and age-appropriate manner. Furthermore, the mentoring process significantly enhances teacher creativity and supports the implementation of interactive, child-centered learning strategies. This study contributes to early childhood education practices by demonstrating how locally available resources and structured mentoring can empower teachers to develop sustainable learning tools. It highlights the importance of contextualized, asset-based interventions in improving both teaching quality and children’s scientific literacy in under-resourced settings.